Características fotossintéticas e de crescimento de plantas de Hymenaea courbaril L. e Handroanthus impetiginosus (MART. EX DC) Mattos submetidas ao alumínio - Vilela, Ana Luiza de Oliveira (2016)
Cerrado vegetation in Brazil occupies approximately 23% of the total area of the country. Most soils of this region consists of Latosols, highly weathered, and Podzolics with severe limitations on vegetation due to low natural fertility of acidic soils and high amount of aluminum. The purpose of this study was to evaluate the different physiological responses and initial vegetative growth of two native species of the Cerrado from different vegetation types, jatobá (Hymenaea courbaril L.) and purple ipê (Handroanthus impetiginosus (Mart. Ex DC.) Mattos) at different Al3+ concentrations. The experiment was conducted in a greenhouse from July 2015 to May 2016 at UFLA Plant Physiology Division. Four months after emergence, 54 individuals of each species were selected and transplanted into six-liter buckets containing the nutrient solution (NS) Hoagland and Arnon for acclimation during 44 days. For the imposition of the treatments were added four different Al3+ concentrations in hydrated aluminum sulphate (Al2 (SO4) 3.14H2O) form at concentrations of 0, 1, 2, and 4 mM throughout 40 days. Aluminum accumulation in leaves increased as larger amounts of Al3+ in the NS, while values of K, N, Fe decreased. A decline in photosynthetic rate (A), stomatal conductance (gs), and transpiration (E) was observed as a higher concentration of Al3+ in the NS, suggesting that aluminum toxicity was determinant in the inhibition of photosynthetic activity of the two species. In jatobá, carboxylation rate (Vc) and electron transport rate (J) showed a decrease, unlike ipê with higher Vc and J at 1mM treatment, but a marked decline at 2 mM. Jatobá chlorophyll in control and 1mM Al3+ were stable, though there was a decrease in other treatments. As observed in ipê, the chlorophyll in the control, 1 mM, and 2 mM concentrations increased gradually whereas at 4 mM the values were stable but below the other treatments. The different concentrations of Al3+ in NS resulted in no significant effect on shoot growth, in jatobá. However, the growth of the aerial part of ipê was greatly affected by the treatment of 4 mM. Jatobá showed no differences for dry mass in leaf, stem, root, and total weight, while in ipê the dry mass of leaves, root, and total weight showed increased tendency at 1mM and a decline in other treatments. So, in jatobá, aluminum did not interfere significantly in their growth, unlike ipê that provided greater growth at 1 mM treatment and decreased at 4 mM, being sensitive to this concentration.